New wave behaviors of the system of equations for the ion sound and Langmuir Waves - Baskonus, Haci Mehmet; Bulut, Hasan (Taylor & Francis Ltd, 2016)
This manuscript focuses on the new wave behaviors of the system of equations for the ion sound wave under the action of the ponderomotive force which results from a nonlinear force that a charged particle experiences in an inhomogeneous oscillating electromagnetic field due to high-frequency field. The sine-Gordon expansion method which is one of the powerful methods has been considered for finding traveling wave solutions of the system of equations for the ion sound wave under the pressure of the Langmuir wave. This algorithm yields new complex hyperbolic function solutions to the system considered in this paper. Wolfram Mathematica 9 has been successfully used throughout the paper for mathematical calculations.
Keywords: Nonlinear Schrodingers Equation; Partial-Differential-Equations; Simplest Equation; (G'/G)-Expansion Method; Computer-Simulation; Expansion Method; Solitons; Complex